PENGARUH MODEL PROBLEM BASED INSTRUCTION TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS X SMA NEGERI PAINAN - Antoni Rahman; Okviani Syafti (STKIP Pesisir Selatan, 2020)
This research was conducted based on the facts showing that the students’ ability in mathematical reasoning problem was still low in class X of SMA Negeri Painan. This could be seen from the result of observation and analysis of their achivement on mathematic reasoning test. To overcome this problem, Problem Based Instruction model was applied. This research was designed for revealing the effect of using Problem Based Instruction model on the students’ reasoning abilities the in class X of SMA Negeri Painan. This was a quasi experimental research. The population of the research was the students in class X of SMA Negeri Painan. By using Random Sampling technique, class X.6 of SMA Negeri 2 Painan was chosen as the experimental group and class X.4 of SMA Negeri 2 Painan was chosen as the control group. The instruments of the research were a questionnaire of creativity to see the students’ creativity in learning and a test to see their ability in mathematic reasoning. Based on the result of the research, some conclusions were drawn. First, the reasoning abilities of the students taught by using Problem Based Instruction model was better than that of students taught by using conventional model. Second, the reasoning ability of the students having high and low kreativity taught by using Problem Based Instruction model was better than that of students taught by using conventional model.